The influence of exogenous steroids on macromolecule uptake by the small intestine of the new-born rat - Daniels, V. G. (1973)
1. Plasma concentrations of cortisol and corticosterone measured by competitive protein binding in rats between 5 and 28 days after birth have been related to the intestinal uptake of [(125)I]polyvinyl pyrrolidone (PVP). 2. Plasma cortisol concentration was consistently low throughout the period studied, but there was an increase in plasma corticosterone concentration at the time (18-21 days) when PVP uptake declined to zero (closure). 3. Injection of a large dose of cortisone acetate 5 days after birth resulted in precocious closure; PVP uptake declined progressively to zero during the 6 days following the injection. Injection of this steroid at 12 days of age caused closure within 4 days. 4. Precocious closure induced by cortisone acetate was closely comparable histologically with natural closure; the decline in PVP uptake was associated with the progressive displacement of vacuolated cells from the villi of the terminal intestine. 5. Injection of corticosterone at either 5 or 12 days after birth also reduced PVP uptake. However, the reduction was transient and uptake returned to control levels some days after the injection. 6. The temporary reduction in PVP uptake following corticosterone injection was not associated with any change in the histological appearance of the small intestine at the light microscope level. 7. The injection of either cortisone acetate or corticosterone was followed by a period of impaired body growth and also a reduction of adrenal weight in animals injected at 12 days but not in animals injected at 5 days.